PENGGUNAAN ALAT DIGITAL BERUPA MEDIA PEMBELAJARAN BERBASIS KAHOOT! SERTA DAMPAKNYA TERHADAP HASIL BELAJAR SISWA SD DALAM KURIKULUM DEEP LEARNING - I Nyoman Sudirman; Ni Luh Putu Krysta Dwi Cahyani; Ni Putu Ayu Widiya Lestari; Ni Putu Revalina Swadya Putri; Ni Komang Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Instructional media plays a crucial role in clarifying materials and enhancing effectiveness in teaching and learning inteactions. The appropriate use of media, whether through printed materials or digital platforms, digital learning media is highly capable of transforming the classroom atmosphere into a more enjoyable, interactive environment, and increasing student motivation. This research method utilizes a literature review by collecting various data and academic publications accredited by Sinta and Google Scholar. This study aims to comprehensively examine the use of Kahoot! - based digital learning media and its various impacts on elementary school student.